Efficacy and Safety of Switching from Low-Dose Statin to High-Intensity Statin for Primary Prevention in Type 2 Diabetes: A Randomized Controlled Trial - Thongtang N (Dove Medical Press, 2020)
Nuntakorn Thongtang, Jirasak Piyapromdee, Natthakan Tangkittikasem, Kittichai Samaithongcharoen, Nithiwat Srikanchanawat, Sutin Sriussadaporn Division of Endocrinology and Metabolism, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Nuntakorn ThongtangDivision of Endocrinology and Metabolism, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, 2 Wanglang Road, Bangkoknoi, Bangkok 10700, ThailandTel +66 2-419-7799Fax +66 2-419-7792Email nuntakorn@hotmail.comIntroduction: Statin intensification is required in patients who have high-risk for cardiovascular events. However, it is unclear if this is needed in whom plasma LDL-C target was achieved with low-dose statin for primary prevention. We investigated the efficacy and safety of switching from low-dose statin to high-intensity statin among type 2 diabetes (T2D) who had achieved plasma LDL-C < 100 mg/dl with low-dose statin treatment.Methods: T2D patients with no atherosclerotic cardiovascular disease who had plasma LDL-C level < 100 mg/dl while taking simvastatin ≤ 20 mg/day were randomized to continue using the same dosage of simvastatin (low-dose statin group; LS) for 12 weeks, or to switch to atorvastatin 40 mg/day for 6 weeks, and then, if tolerated, to atorvastatin 80 mg/day for 6 weeks (high-intensity statin group; HS). Biochemical test and adverse events were evaluated at baseline, 6 weeks, and 12 weeks.Results: One hundred and fifty patients (76 LS, 74 HS, mean age 58.9± 8.9 years, 72% female) were included. The mean baseline plasma LDL-C level on statin was slightly higher in the HS group (71.9± 13.6 vs. 68.1± 14.2 mg/dl, p=0.09). The HS group had a significantly lower plasma LDL-C level at both 6 and 12 weeks (both p< 0.001). Plasma LDL-C < 40 mg/dl was found more frequently in the HS group (23.0% vs. 3.9%, p< 0.001). Discontinuation of statin due to adverse effects was more frequent in the HS group (5.4% vs. 1.3%, p=0.38 for atorvastatin 40 mg/day, 12.2% vs. 1.3%, p=0.03 for atorvastatin 80 mg/day). No serious adverse events were observed in either group.Conclusion: Switching from low-dose statins to high-intensity statins resulted in a significant reduction in plasma LDL-C levels, and was fairly well tolerated during a 12-week study period.Keywords: efficacy, safety, high-intensity statin, primary prevention, Thai patients, type 2 diabetes